2017
DOI: 10.1016/s0140-6736(17)30751-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinically significant bleeding with low-dose rivaroxaban versus aspirin, in addition to P2Y12 inhibition, in acute coronary syndromes (GEMINI-ACS-1): a double-blind, multicentre, randomised trial

Abstract: SummaryBackground Dual antiplatelet therapy (DAPT), aspirin plus a P2Y12 inhibitor, is the standard antithrombotic treatment following acute coronary syndromes. The factor Xa inhibitor rivaroxaban reduced mortality and ischaemic events when added to DAPT, but caused increased bleeding. The safety of a dual pathway antithrombotic therapy approach combining low-dose rivaroxaban (in place of aspirin) with a P2Y12 inhibitor has not been assesssed in acute coronary syndromes. We aimed to assess rivaroxaban 2·5 mg t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(136 citation statements)
references
References 35 publications
(44 reference statements)
2
123
0
11
Order By: Relevance
“…24 25 Most patients who are asymptomatic with mild to moderate physical activity-walking two flights of stairs or walking briskly for a few minutes-should be able to resume sexual activity around a week after an uncomplicated myocardial infarction. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Information about sexual activity is usually included in cardiac rehabilitation programmes.…”
Section: Sexual Activitymentioning
confidence: 99%
“…24 25 Most patients who are asymptomatic with mild to moderate physical activity-walking two flights of stairs or walking briskly for a few minutes-should be able to resume sexual activity around a week after an uncomplicated myocardial infarction. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Information about sexual activity is usually included in cardiac rehabilitation programmes.…”
Section: Sexual Activitymentioning
confidence: 99%
“…The more recently published GEMINI ACS 1 (A Study to Compare the Safety of Rivaroxaban Versus Acetylsalicylic Acid in Addition to Either Clopidogrel or Ticagrelor Therapy in Participants With Acute Coronary Syndrome) study was a phase II randomized trial of 3037 patients with ACS comparing aspirin or rivaroxaban 2.5 mg BID in addition to clopidogrel or ticagrelor 27. The primary end point was non–coronary artery bypass grafting–related TIMI clinically significant bleeding.…”
Section: Beyond Dapt: Triple‐therapy Combinations In Acsmentioning
confidence: 99%
“…Conversely, in the Anti-Xa Therapy to Lower Cardiovascular Events in Addition to Standard Therapy in Subjects with Acute Coronary Syndrome (ATLAS-ACS-2) study, a very low-dose of rivaroxaban (2.5 mg twice daily) resulted in significantly less ischaemic events at the price of increased major and intracranial bleeding 19. In further scrutiny of a safer rivaroxaban-based strategy for patients with ACS, a phase II study recently reported the same risk of clinically significant bleeding with very low-dose rivaroxaban and a P2Y 12 inhibitor (ie, without aspirin) compared with DAPT, but whether this strategy is also similarly effective remains uncertain 20. Rivaroxaban is currently indicated by the European Medical Agency for the prevention of atherothrombotic events in patients with ACS and elevated cardiac biomarkers and is given by clinical practice guidelines a class IIb recommendation for combination therapy with DAPT 21.…”
Section: Triple or Dual Antithrombotic Therapy In The Era Of Noacsmentioning
confidence: 99%